Examining adherence to American Urological Association (AUA) guidelines in men’s health: Insights from the New York section AUA survey - Hunter Hernandez; John Fastenau; Ari Bernstein; Hossein Sadeghi-Nejad (Investigative and Clinical Urology, 2025)
Purpose: With the introduction of the AUA Quality Registry (AQUA), physician practice styles and adherence to clinical guidelines are under closer scrutiny. While adherence is critical for optimal healthcare, it has not been studied in men’s health. This survey-based study assessed adherence to American Urological Association (AUA) clinical guidelines on erectile dysfunction (ED), Peyronie’s disease, priapism, infertility, and ejaculatory disorders among members of the New York section of the AUA. Materials and Methods: An anonymous questionnaire was emailed to members, covering five non-oncologic men’s health guideline categories. Each category included two to four specific guidelines, with responses recorded on a Likert scale. Respondents could provide rationale for their answers or omit questions if they did not treat a specific condition. Results: Among 82 urologists, most treated ED and ejaculatory dysfunction but less commonly treated Peyronie’s, priapism, and infertility. Some guidelines were frequently not followed. For instance, 57% never prescribed tramadol or α1-adrenoreceptor antagonists for premature ejaculation after first-line therapy failure. Half never performed in-office intracavernosal injection tests for Peyronie’s. For priapism, 52% never used ultrasound in initial evaluations, and 45% rarely referred men with ED to mental health professionals. Conclusions: This pilot study highlights generally high adherence to AUA guidelines but identifies gaps in areas driven by expert opinion. Findings suggest a need for targeted educational initiatives, particularly in Peyronie’s diagnosis and mental health integration for ED, to enhance patient care and outcomes. Such initiatives are crucial in refining the approach to men’s health, ultimately enhancing patient care and outcomes.